Common brain areas engaged in false belief reasoning and visual perspective taking: a meta-analysis of functional brain imaging studies - Schurz, Matthias; Aichhorn, Markus; Martin, Anna; Perner, Josef (Frontiers in Human Neuroscience, 2013)
We performed a quantitative meta-analysis of functional neuroimaging studies to identify brain areas which are commonly engaged in social and visuo-spatial perspective taking. Specifically, we compared brain activation found for visual-perspective taking to activation for false belief reasoning, a task which requires awareness of perspective to understand someone’s mistaken belief about the world which contrasts with reality. In support of a previous account by Perner & Leekam (2008), a meta-analytic conjunction analysis found activation for false belief reasoning and visual perspective taking in the left but not the right dorsal temporo-parietal junction. This fits with the idea that the left dorsal TPJ is responsible for representing different perspectives in a domain-general fashion. Moreover, the conjunction found activation in the precuneus and the left middle occipital gyrus close to the putative Extrastriate Body Area. The precuneus is linked to mental-imagery processes, which may aid in the construction of a different perspective. The Extrastriate Body Area may be engaged due to imagined body-transformations when another’s viewpoint is adopted.